The Diurnal Nature of Future Extreme Precipitation Intensification. Issue 13 (10th July 2019) - Meredith, Edmund P.; Ulbrich, Uwe; Rust, Henning W.
Abstract: Short‐duration, high‐impact precipitation events in the extratropics are invariably convective in nature, typically occur during the summer, and are projected to intensify under climate change. The occurrence of convective precipitation is strongly regulated by the diurnal convective cycle, peaking in the late afternoon. Here we perform very high resolution (convection‐permitting) regional climate model simulations to study the scaling of extreme precipitation under climate change across the diurnal cycle. We show that the future intensification of extreme precipitation has a strong diurnal signal and that intraday scaling far in excess of overall scaling, and indeed thermodynamic expectations, is possible. We additionally show that, under a strong climate change scenario, the probability maximum for the occurrence of heavy to extreme precipitation may shift from late afternoon to the overnight/morning period. We further identify the thermodynamic and dynamic mechanisms which modify future extreme environments, explaining both the future scaling's diurnal signal and departure from thermodynamic expectations. Plain Language Summary: The most intense rainfall events—predominantly warm‐season thunderstorms—are predicted to become more intense in a warmer climate. Thunderstorms occur most often in the late afternoon, at the peak of the diurnal convective cycle. How the future intensification of extreme rainfall events will interact with the diurnal convective cycle remains uncertain. Here we employ the newest generation of climate models—convection‐permitting climate models—to study this question. Due to their high spatial resolution, convection‐permitting models can directly simulate convective processes (which was not possible with older generations of climate models), making them an ideal tool for studying changes in intense thunderstorms. We find that the future intensification of intense rainfall events is not uniform across all hours of the day but instead has a strong diurnal signal, with the midmorning period seeing the greatest intensification. An implication of this diurnally unequal intensification is that under a strong climate change scenario the diurnal convective maximum for extremes may, in some regions, shift from late afternoon to the overnight/morning period. Key Points: Future precipitation scaling has a strong diurnal signal Future diurnal convective maximum for extremes may shift to overnight/morning Stability indexes are unreliable proxies for future scaling of extreme rainfall